CLIMATE VILLAGE STRATEGY IN MADIUN AS A FORM OF CLIMATE CHANGE MITIGATION TOWARDS A SMART ENVIRONMENT - Annita Yuli Mayasari; Maria Theresia Sri Budiastuti; Agung Hidayat (GeoEco, 2025)
The Ministry of Environment and Forestry initiated the Climate Village Program (ProKlim) to increase community involvement in climate change adaptation and mitigation. This study aims to analyse the Climate Village Program implementation strategy in Madiun City as a form of climate change mitigation and the embodiment of the Smart Environment concept. The qualitative research approach uses data collection techniques through field observations, in-depth interviews, and questionnaires distributed to 96 respondents from 24 climate villages spread across Madiun City. The main informants consisted of representatives of the environmental service, community leaders, and ProKlim actors. The study results showed that the ProKlim implementation strategy received positive support from the community, local government, and the private sector. The main strategies include strengthening local institutions, integrating environmentally friendly technology, and increasing community capacity through environmental education. However, private sector participation and technology utilisation still need to be improved for more efficient environmental management. These findings confirm that multi-stakeholder collaboration and community-based approaches are the keys to success in realising climate-resilient cities through the Smart Environment concept.